Efficient adsorption removal of anionic dyes by an imidazolium-based mesoporous poly(ionic liquid) including the continuous column adsorption-desorption process. (June 2021) - Lin, Ju; Su, Tiezhu; Chen, Jiawen; Xue, Tianwei; Yang, Shuliang; Guo, Peiwen; Lin, Hongying; Wang, Hongtao; Hong, Yanzhen; Su, Yuzhong; Peng, Li; Li, Jun
Abstract: The mesoporous poly( N, N ′-methylene-bis(1-(3-vinylimidazolium)) chloride), labeled as PDVIm-Cl, with double anions (Cl − ) and low monomer molecular weight was synthesized and applied in the adsorption of anionic dyes (acid orange 7 (AO7), sunset yellow (SY), reactive blue 19 (RB19), congo red (CR)). Due to the mesoporous structure, abundant Cl − and positively charged imidazole rings, the poly(ionic liquid) (PIL) exhibited superior adsorption ability towards anionic dyes. What is more, the RB19 adsorption by PDVIm-Cl could achieve the highest capacity (2605 ± 254 mg g −1 ) which was nearly twice higher than the maximum adsorption capacity of the previously reported materials. All the adsorption kinetic data and isotherms fitted well with the pseudo second-order model and Langmuir-Freundlich model. To better explore the practical potential of the PIL for dye adsorption, the adsorption under different pH values and column adsorption performances were also evaluated. Results showed that PDVIm-Cl exhibited high removal efficiencies for anionic dyes over a wide pH range (2−10). Also, the great reusability could be well demonstrated by the achievable continuous column adsorption-desorption process. It is worth mentioning that the regeneration could be realized with very little desorbent which was far less than the adsorption volume flowing through the column and the desorption efficiency was well maintained after three consecutive cycles. At last, the adsorption mechanism was explored by experiments combined with quantum chemical calculations and showed anionic dyes adsorption by PDVIm-Cl was a joint process dominated by the ion exchange, electrostatic interaction, hydrogen bond and π-π stacking. Highlights: PDVIm-Cl is capable to adsorb various anionic dyes with high capacities. PDVIm-Cl shows unprecedented adsorption capacity of 2605 ± 254 mg g −1 for RB19 dye. PDVIm-Cl could be used to adsorb different anionic dyes in a wide range of pH. PDVIm-Cl can easily realize continuous column adsorption-desorption process. The adsorption mechanism is studied by experimental and theoretical calculations.